High-throughput site-directed mutagenesis using oligonucleotides synthesized on DNA chips - Saboulard, Didier (BioTechniques, 2005)
Site-directed mutagenesis has greatly helped researchers both to understand the precise role of specific residues in coding sequences and to generate variants of proteins that have acquired new characteristics. Today's demands for more complete functional cartographies of proteins and advances in selection and screening technologies require that site-directed mutagenesis be adapted for high-throughput applications. We describe here the first generation of a library of single and multiple site-directed mutants using a mixture of oligonucleotides synthesized on DNA chips. We have used the human interleukin 15 (IL15) gene as a model, of which 37 codons were simultaneously targeted for substitution by any of eight possible codons. Ninety-six clones were sequenced, exhibiting a broad spectrum of targeted substitutions over the whole gene length with no unwanted mutations. Libraries produced using such pools of oligonucleotides open new perspectives to direct the evolution of proteins in vitro, by enabling the simple, rapid, and cost-effective generation of large tailor-made genetic diversities from any gene